Short- and long-term effects of individualized enteral protein supplementation in preterm newborns - Ergenekon, Ebru; Soysal, Şebnem; Hirfanoğlu, İbrahim and Baş, Veysel and Gücüyener, Kıvılcım and Turan, Özden and Beken, Serdar and Kazancı, Ebru and Türkyılmaz, Canan and Önal, Esra and Koç, Esin and Atalay, Yıldız (The Turkish Journal of Pediatrics, 2013)
The aim of this retrospective study was to assess the need for additional enteral protein supplementation in preterm newborns with gestational age (GA) ≤32 weeks after full enteral feeds with either fortified breast milk (FBM) or preterm formula (PF) were reached, and to determine the effects of additional protein on physical and neurological development. After the standard early total parenteral nutrition (TPN) and reaching full enteral nutrition with 150-160 ml/kg/day, preterms were assessed for the requirement of additional protein based on serum blood urea nitrogen (BUN)/prealbumin levels. Additional enteral protein was given for BUN